Some of the Immunogenetics Aspects of Aging - Bushra N. Al Hadra (Journal of Biomedical & Clinical Research)
The human life span could be influenced by the combined effect of environment, lifestyle, and genetic factors. Twin and family studies suggest that our genes control up to 25% of the lifespan. The aging immune system undergoes age-associated changes at multiple levels, resulting in a gradual loss of its ability to protect the organism against infections, low vaccine responses, and an increased probability of developing autoimmune diseases and malignancies. The highly polymorphic HLA complex is one of the major gene candidates associated with aging due to its crucial role in developing adaptive immunity and protecting the organism. Most of the data available have so far demonstrated a positive association with healthy aging for HLA alleles/haplotypes as protective against malignancies, autoimmune diseases, and conferring better control and response to infections. One of aging’s main manifestations is the chronic, low-grade inflammatory state observed in older people, caused by an imbalance between pro- and anti-inflammatory cytokines. In general, it is has been agreed that longevity is related to anti-inflammatory genotype profiles. With advanced age, changes also occur in the B cell repertoire, which significantly affects the humoral immunity and leads to inadequate responses to infections and vaccines in the elderly. New genetic biomarkers associated with aging are being explored and discovered, contributing to a better understanding of the molecular processes underlying the immune dysfunction related to aging and developing strategies for rejuvenating the immune system based on immune-risk phenotypes.